Water Repellency in Hydrophobic Nanocapsules—Molecular View on Dewetting. Issue 22 (29th April 2014) - Müller, Achim; Garai, Somenath; Schäffer, Christian; Merca, Alice; Bögge, Hartmut; Al‐Karawi, Ahmed Jasim M.; Prasad, Thazhe Kootteri
Abstract The hydrophobic effect plays a major role in a variety of important phenomena in chemistry, materials science and biology, for instance in protein folding and protein–ligand interactions. Studies—performed within cavities of the unique metal oxide based porous capsules of the type {(pentagon)12(linker)30}≡{(W)W5}12{Mo2(ligand)}30 with different acetate/water ligand ratios—have provided unprecedented results revealing segregation/repellency of the encapsulated "water" from the internal hydrophobic ligand walls of the capsules, while the disordered water molecules, interacting strongly with each other via hydrogen bonding, form in all investigated cases the same type of spherical shell. The present results can be (formally) compared—but only regarding the repellency effect—with the amazing "action" of the (super)hydrophobic Lotus (Nelumbo) leaves, which are self‐cleaning based on water repellency resulting in the formation of water droplets picking up dirt. The present results were obtained by constructing deliberately suitable hydrophobic interiors within the mentioned capsules.